Efikasi Diri Mahasiswa Bimbingan Konseling Islam dalam Mempersiapkan Karir - Intan Maisara; Zulkarnain Zulkarnain; Rizky Andana Pohan (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2020)
One important component in an individual's life is self-efficacy. Self-efficacy is one aspect of knowledge about self or self-knowledge that is most influential in everyday human life. So that every individual should have good self-efficacy to prepare for a future career. The purpose of this study is to find out how the self-efficacy of IAIN Langsa Islamic counseling guidance students in preparing for a career. The problem examined in this study is how the self-efficacy of IAIN Langsa Islamic counseling guidance students in preparing for a career. In conducting this research researchers used a qualitative method with the type of phenomenological study, the determination of the informants in this study was determined using purposive sampling techniques, in processing the research data using the filling system technique. The filling system method is a method in which the researcher feels that the collected data is sufficient so the analysis is performed. The results of the study showed that the self-efficacy of IAIN Langsa Islamic counseling students in preparing for a career was classified as good. Islamic counseling students already understand what the world of counseling is like, what it works like, and have prepared steps for future career preparation. Scientifically at least Islamic counseling students already have insight into the world of counseling so that it helps students to achieve good self-efficacy